Crisis informatics: a systematic evaluation - Bukar, Umar Ali; A. Jabar, Marzanah; Sidi, Fatimah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Crisis management and communication are increasingly being challenged by the impact of social media as a forum for crisis communication. Among the many roles that crisis management services embrace, managing outreach information and communication are increasingly important. This study presents a systematic review of articles pertaining to the application of social media to support crisis management. Our review presents that, Situational Crisis Communication Theory (SCCT) is the most dominant theory for crisis communication and twitter is the dominant social network site. Also, the review identifies decision-making, community resilience, privacy issues, information sharing and seeking, social media based crisis communication for future studies.